2004
DOI: 10.1207/s15324834basp2604_5
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to the Imputation of Prejudice

Abstract: In this research, I examined how people deal with imputations of racial prejudice. In one experiment, I explored participants' reaction to hypothetical imputations, and in one experiment, I explored participants' reactions to imputations from ostensibly real people. Results indicate that Whites are keenly concerned about other peoples' perceptions of their racial attitudes, especially when those other people are Black. Results also illuminate Whites' perceptions of Blacks' perceptions of prejudice. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 8 publications
1
24
1
Order By: Relevance
“…Finally, in two experiments we found evidence that the reason acknowledging causes people to form a more positive evaluations of character than denying does is because acknowledging signals more of a learning orientation than denying does. Thus, while research shows that people often deny prejudice (e.g., Czopp et al, 2006;Winslow et al, 2004), our work reveals the upside of doing just the opposite.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Finally, in two experiments we found evidence that the reason acknowledging causes people to form a more positive evaluations of character than denying does is because acknowledging signals more of a learning orientation than denying does. Thus, while research shows that people often deny prejudice (e.g., Czopp et al, 2006;Winslow et al, 2004), our work reveals the upside of doing just the opposite.…”
Section: Discussioncontrasting
confidence: 52%
“…Celebrities, politicians, and other public figures are notorious for their denials, and yet, people not in the public eye also deny prejudice frequently. For example, when participants in studies are confronted for making racially prejudiced statements, most respond by denying that race affected their behavior, denying they are a racist person, or with hostility (Czopp et al, 2006; see also Czopp & Monteith, 2003;Winslow, 2004). Here, we define acknowledging prejudice as a verbal response to confrontation that recognizes one's behavior was influenced by bias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…power and metastereotyping 4 will behave more benevolent toward them than when we think they do not (see also Kamans, Gordijn, Oldenhuis, & Otten, 2008;Sigelman & Tuch, 1997;Winslow, 2004).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…People's private personal values refl ect the internal motivation to not be prejudiced, while publicly expressed attitudes refl ect the external motivation to not be perceived as prejudiced. Numerous studies suggest that the external motivation to respond without prejudice is powerful (Bradley-Geist, King, Skorinko, Hebl, & McKenna, 2010;O'Brien et al, 2010;Shelton, 2003;Winslow, 2004) and that external motivations can preclude private attitudes. Van Boven (2000), for example, found that situational pressure to appear unprejudiced led people to publicly praise and support politically correct programs such as affi rmative action despite holding diff erent private thoughts and feelings.…”
Section: Motivations For Appearing Diversementioning
confidence: 99%